Determinants of cervical cancer screening uptake among women attending selected family planning clinics in Ibadan, Oyo State, Nigeria. (2020)
Background: Cervical cancer screening (CCS) continuously has low awareness and is poorly utilized in developing countries despite higher incidence of cervical cancer (CC). Increasing incidence of CC has been associated with late reporting of symptoms, ignorance about the disease, and its preventive measures. This study was conducted to further investigate the determinants of CCS uptake among women attending selected family planning clinics in Ibadan, Nigeria. Materials and Methods: Adopting a cross‑sectional design, 205 consenting respondents attending family planning clinics were interviewed using an interviewer‑administered questionnaire. The data collected were analyzed using Statistical Package for the Social Sciences version 21. The hypotheses were tested using Chi‑square, odds ratio, and logistic regression at P < 0.05. Results: The mean age of the respondents was 33 ± 8 years; 176 (85.9%) were married and 72 (35.1%) had tertiary education. Although 71% of the respondents were aware of CC, only 37.1% had good knowledge and 16.1% had previously utilized CCS. About two‑thirds (68.8%) of the respondents were willing to uptake CCS, except for perceived barriers such as lack of understanding of the disease and inadequate information about the services coupled with limited availability of the CCS services. There was a significant association between uptake of CCS and knowledge (χ2 = 17.944, P < 0.001), education (χ2 = 7.724, P < 0.024), and income (χ2 = 32.22, P < 0.001). On logistic regression, the uptake CCS remained influenced mainly by income of >40,000 Naira (OR = 5.355, CI = 1.678–17.083) and knowledge (OR = 3.112, CI = 1.247–7.768). Conclusion: Family planning clinics are readily available centers for increasing the knowledge base of the women on the need for regular CCS. This needs to be duly incorporated into our routine services.